Show don't tell ebook Stories. - Sittenfeld, Curtis (2025)
NATIONAL BESTSELLER • The bestselling author of Eligible and Romantic Comedy “blends acerbic wit, shrewd insight and sharp-eyed observation [in this] bravura collection” ( The Washington Post ), including a story that revisits the main character from her iconic novel Prep “Each of these witty, intelligent stories is a slice of modern life.” —People A New York Times Book Review Editors’ Choice In her second story collection, Sittenfeld shows why she’s as beloved for her short fiction as she is for her novels. In these dazzling stories, she conjures up characters so real that they seem like old friends, laying bare the moments when their long held beliefs are overturned. In “The Patron Saints of Middle Age,” a woman visits two friends she hasn’t seen since her divorce. In “A for Alone,” a married artist embarks on a creative project intended to disprove the so-called Mike Pence Rule, which suggests that women and men can’t spend time alone together without lusting after each other. And in “Lost but Not Forgotten,” Sittenfeld gives readers of her novel Prep a window into the world of her beloved character Lee Fiora, decades later, when Lee attends an alumni reunion at her boarding school. Hilarious, thought-provoking, and full of tenderness for her characters, Sittenfeld’s stories peel back layer after layer of our inner lives, keeping us riveted to the page with her utterly distinctive voice.